Analisis Pembelaan Terpaksa Korban Tindak Pidana Pembegalan yang Dijadikan Tersangka Menurut Tinjauan Viktimologi - Utami, Pingky (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Price rounding is the practice of adjusting the price of goods by rounding it This research examines the phenomenon of victims of criminal acts of robbery being made suspects after carrying out forced defense actions. In this context, the analysis is carried out based on a victimology perspective which highlights the role and position of the victim in the legal process. Compulsory defense is often recognized in criminal law as a legitimate measure to protect oneself from an unavoidable threat. However, the complexity of certain cases means that victims who are defending themselves from brutal attacks become the ones who are blamed and made suspects. This research uses a normative juridical method with a case approach, and utilizes literature studies to understand how victimology laws and policies are applied in situations like this. This research recommends policies that are fairer and more sensitive to victims in the context of forced defense, as well as increasing legal awareness of law enforcement officers regarding aspects of victimology.